A dangerous loop - Ahmad, Saqib; Bragg, Damian; Zaitoun, Abed; Lobo, Dileep N. (Wiley, 2016)
Key Clinical Message: A 76-year-old man developed a hemoperitoneum after ERCP for choledocholithiasis. He underwent a laparotomy and splenectomy for a capsular tear at the splenic hilum, a rare complication of ERCP. “Bowing” of the endoscope with torsion on the greater curvature of the stomach may lead to shear forces causing splenic injury.